Comparative Study on In Vitro Culture of Mouse Bone Marrow Mesenchymal Stem Cells - Yuxin Hu; Bin Lou; Xiafang Wu; Ruirui Wu; Huihui Wang; Lanyue Gao; Jingbo Pi; Yuanyuan Xu (Stem Cells International)
In vitro culture of mesenchymal stem cells (MSCs) from mouse bone marrow (BM) has been hampered because of the low yield of MSCs during isolation and the contamination of hematopoietic cells during expansion. The lack of specific mouse BM-MSC markers increases the difficulty. Several techniques have been reported to improve the purity and in vitro growth of mouse BM-MSCs. However, systematic report on comparison of characteristics in primary BM-MSCs between different culture conditions is rare. Here, we studied the effects of oxygen concentrations and initial medium replacement intervals, along with cell passages, on mouse BM-MSCs isolated with differential adhesion method. BM-MSCs exhibited elevated proliferative and clonogenic abilities in 5% oxygen compared with 10% and 21% oxygen, as well as a better expression of the MSC marker Sca-1. Adipogenic and osteogenetic differentiation of BM-MSCs can be observed in both 21% and 5% oxygen. Adipogenic differentiation appeared stronger under normoxia conditions. BM-MSCs showed increased proliferative capacity and adipogenic/osteogenetic differentiation potential when initial medium replacement interval was 4 days compared with 1 day. As passage number increased, cells were more MSC-like in morphology and in expression of surface markers (positive for CD29, CD44, and Sca-1 and negative for CD11b, CD19, and CD45). These data provide new insight into optimizing the culture method and understanding the biological characteristics of mouse BM-MSCs during in vitro expansion.